2012
DOI: 10.1159/000334488
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Herbs and Conventional Drugs: Overview of the Clinical Data

Abstract: This article provides an overview of the clinical evidence of interactions between herbal and conventional medicines. Herbs involved in drug interactions – or that have been evaluated in pharmacokinetic trials – are discussed in this review. While many of the interactions reported are of limited clinical significance and many herbal products (e.g. black cohosh, saw palmetto, echinacea, hawthorn and valerian) seem to expose patients to minor risk under conventional pharmacotherapy, a few herbs, notably St. John… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 416 publications
(233 reference statements)
3
133
0
8
Order By: Relevance
“…Altogether, this review could not identify studies showing a clinically relevant interaction effect of valerian. This confirms pharmacovigilance reviews of herbal medicinal products, which do not mention valerian at all [58][59][60] or claim valerian as safe [16,[27][28][29][30][31]. Block et al [5] specifically pointed out that valerian is safe and efficient in patients undergoing cancer therapy.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Altogether, this review could not identify studies showing a clinically relevant interaction effect of valerian. This confirms pharmacovigilance reviews of herbal medicinal products, which do not mention valerian at all [58][59][60] or claim valerian as safe [16,[27][28][29][30][31]. Block et al [5] specifically pointed out that valerian is safe and efficient in patients undergoing cancer therapy.…”
Section: Discussionsupporting
confidence: 60%
“…While the side effect profile therefore is benign, a potential for adverse drug interactions has been claimed by some reviews [26], while other reviews did not [18,[27][28][29][30][31][32], so that a reevaluation of the existing evidence is necessary.…”
Section: Efficacy and Safety Of Valerian Extractsmentioning
confidence: 99%
“…These effects could be more severe in people with cardio vascular disease. The current findings add to a growing body of litera ture on risk of the concomitant intake of medicinal plants and drugs, [35][36][37][38] further experimental investigations are needed to promote the rational use of the herbal medicine.…”
Section: Discussionmentioning
confidence: 93%
“…[6][7][8][9][10][11][12][13][14] and several others biological effects. 30,31 In recent years, there has been an increasing amount of literature on the interaction between some drugs and medicinal plants and its adverse reactions [35][36][37][38] However, there is no evidence that Maytenus macrocarpa could have effects with concomitant administration of drugs such as propranolol. Studies have reported a dual effect of propranolol on temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that 3.7 million Australians may be at risk of CAM-drug interactions due to concurrent use of CAM and pharmaceutical drugs [31]. Concomitant CAM-drug use is further compounded by the general public's belief that CAM, particularly herbal medicines, are considered safe because they are natural [32], and limited dialogue about CAM use between patients and health care providers [20,21,33,34]. CAMs that may interfere with the effect of anticoagulant or antiplatelet therapy are of particular concern considering the prevalence of these therapies for the treatment of cardiovascular disease.…”
Section: The Importance Of Cam In Australian Clinical Practicementioning
confidence: 99%